DAMPAK PENGGUNAAN METODE TUTOR SEBAYA TERHADAP KUALITAS BELAJAR SISWA PADA PEMBELAJARAN TARI DI SMP NEGERI 17 PADANG - Annisa, Rizka; Indrayuda, Indrayuda (SENDRATASIK UNP, 2019)
AbstractÂ This study aims to describe the impact of the use of peer tutor method toward the quality of the students learning in dance learning at class VIII.5 in SMP Negeri 17 Padang. This type of study was a qualitative with using descriptive method. The object in this study was the students of class VIII.5 in SMP Negeri 17 Padang that totaling 30 students with material on applying floor patterns to dance moves. The main instrument in this study was the researcher and it was assisted by using supporting instruments such as observation sheets, notebooks, and camera. These types of data used primary data and secondary data. Techniques of data collection were carried out by doing observation, interview, literature study and documentation. Data was analyzed with some steps, namely collecting, reducting; displaying; and verificating data. The result shows that the use of the peer tutor method in dance learning at class VIII. 5 is well done. The result is achieved by the students from the daily test scores that 96% of the students have completed in learning material about the application of the floor pattern to dance moves. This proves that the impact of the use of peer tutor method can improve the quality of the student learning in dance learning in SMP Negeri 17 Padang. Although there are problems in learning to practice the dance moves, the teacher who teaches still has a solution for the students so that the quality of the student learning still improves good results.Â Keywords: Peer Tutor Method, Learning Quality, and Dance Learning.